Synthetic molecular walkers - Delius, Max von (The University of Edinburgh, 2010)
The work presented in this thesis was inspired by one of the most fascinating classes of naturally occurring molecules: bipedal motor proteins from the kinesin, dynein and myosin superfamilies walk along cellular tracks, carrying out essential tasks, such as vesicle transport, muscle contraction or force generation. Although a few synthetic mimicks based on DNA have been described, small-molecule analogues that exhibit the most important characteristics of the biological walkers were still missing until recently. In this thesis, the design, synthesis and operation of several small-molecule walker-track systems is described. All presented systems share a similar molecular architecture, featuring disulfide and hydrazone walker-track linkages, yet deviate fundamentally in the mechanism and energy input that is required for directional walker transport. Chapter I includes an overview of the biological walker proteins, as well as a comprehensive review of the DNA-based mimicks published to date. A set of fundamental walker characteristics is identified and special emphasis is given to the underlying physical mechanisms. Chapter II describes a series of experiments, which lay the groundwork for all smallmolecule walker systems presented in the following Chapters of this thesis. The mutually exclusive nature of disulfide and hydrazone exchange under basic and acidic reaction conditions, was demonstrated using an unprecedented type of macrocycle. The first small-molecule walker-track system is described in Chapter III. Due to the passive nature of both the track and the walker unit, an oscillation of acidic and basic reaction conditions led to a directionally un-biased, intramolecular ‘diffusion’ of the walker unit along the track. Using an irreversible redox-reaction for one of the foot-track exchange reactions conferred a certain degree of directionality to the walking sequence, with the oxidant iodine providing the chemical fuel for the underlying Brownian information ratchet mechanism. Chapter IV contains a comprehensive investigation of the dynamic properties of a series of walker-track conjugates derived from the walker-track conjugate presented in Chapter III. The most significant observation was that ring strain appears to be a requirement for the emergence of directional bias, a phenomenon that has also been found in biological walkers. In Chapter V a different type of walker-track conjugate is described, in which the track plays an active role and light is used as the fuel required for directional walker transport. The key for achieving directionality was the presence of a stilbene unit as part of the molecular track, through which ring strain could be induced in the isomer where the walker unit bridges the E-stilbene linkage. Significantly, the underlying Brownian energy ratchet mechanism allowed walker transport in either direction of the molecular track. Chapters II to V are presented in the form of articles that have recently been published or will be published in due course in peer-reviewed journals. No attempt has been made to re-write this work out of context, other than to avoid repetition, insert crossreferences to other Chapters (where appropriate) and to ensure consistency of presentation throughout this thesis. Chapters II, III, IV and V are reproduced in the Appendix, in their published formats. The Outlook contains closing remarks about the scope and significance of the presented work as well as ideas for the design and operation of a next generation of small-molecule walkers, some of which are well under way in the laboratory.
Keywords: bipedal motor proteins; kinesin; dynein; myosin; cellular tracks; biological walkers